(untitled) (Indian Journal of Arid Horticulture, 2025)
The cultural operations like stop of irrigation during winter season and binding of main trunk up to 5 cm width by jute thread and spraying of ethrel at 500 and 1000 ppm concentration increased the fruit set %, yield and take minimum time to mature the fruit than control during the both the year 2007-08 and 2008-09. The interaction all treatment (T, ) i.e. stop of irrigation during December to February, girdling by the binding of main trunk up to 5 cm width with the help of jute thread, spraying of 500 ppm and of 500 ppm ethrel was most effective to increased the fruit set (69.41 to71.02 %), yield (140.58 to 145.23 kg/tree) and take minimum time (215.26 -216.71 days) to mature the fruit during both the year. The treatment (T, ) was also most effective to increase the fruit weight (46.02 to 46.52 g), TSS % (10.54 to 10.55) and shelf life (15.01 to 15.23 days) of fruit than other treatment and control. Key words: Aonla, binding of main trunk, ethrel, girdling, shelflife